Inequalities via generalized h-convex functions - Noor, M. A.; Noor, K. I.; Safdar, F. (Issues of analysis, 2018)
In the paper, we establish some new Hermite-Hadamard-Fej´er type inequalities via generalized h-convex functions, Toader-like convex functions and their variant forms. Several special cases are also discussed. Results proved in this paper can be viewed as significant new contributions in this field.